The Phenomenon of Family Content Creators and Its Implications for the Formation of a Maslahah Family - Hidayatun Ulfa; A’yunin Nadhiroh; Braham Maya Baratullah (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
The rapid development of social media has given rise to the phenomenon of family content creators, referring to families who actively share their domestic lives through various digital platforms. This phenomenon offers opportunities for education, entertainment, and economic gain; however, it also raises concerns regarding family privacy, the culture of oversharing, and the potential exploitation of children. This study aims to analyze the legal ethics of the family content creator phenomenon from the perspective of Islamic Family Law and to examine its influence on the realization of a maslahah (harmonious and welfare-oriented) family. The research employs a qualitative descriptive approach using the library research method. Data were collected from books, scholarly journals, articles, and other relevant literature and analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that the activities of family content creators are fundamentally permissible in Islam, provided that they uphold the principles of maslahah, safeguard family privacy, protect children's rights, and comply with Islamic legal and ethical values. Such activities may generate positive outcomes, including educational benefits, inspiration, strengthened social relationships, and economic opportunities that contribute to the establishment of a maslahah family. Nevertheless, when carried out excessively without due consideration of Islamic ethical and legal boundaries, these activities may result in negative consequences, such as violations of privacy, child exploitation, social pressure, and the disruption of family harmony. Therefore, the use of social media within the family context should be exercised wisely, proportionately, and responsibly to ensure alignment with the objectives of family protection and welfare as prescribed in Islam.